Differentiate f(x) = (x+3)/(2x-5) using the quotient rule.

For a quotient f(x) = u(x)/v(x), the derivative is f'(x) = (vu'(x) - uv'(x))/v(x)2. Applying this to the given function, we find u(x) = x+3 and v(x) = 2x-5. So, u'(x) = 1 and v'(x) = 2. We can then put these into the expression for the quotient rule: f'(x) = ((2x-5)*1 - (x+3)*2)/(2x-5)= (2x - 5 - 2x - 6)/(2x-5)2 = -11/(2x-5)2.

Answered by Sara R. Maths tutor

4914 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do you split a fraction into partial fractions?


A circle with centre C has equation: x^2 + y^2 + 20x - 14 y + 49 = 0. Express the circle in the form (x-a)^2 +(y-b)^2=r^2. Show that the circle touches the y-axis and crosses the x-axis in two distinct points.


How can I find all the solutions to cos(3x) = sqrt(2)/2 for 0<=x<=2pi ?


Given the equation 0=5x^2+3xy-y^3 find the value of dy/dx at the point (-2,2)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences